The effect of differentiated instruction on academic achievement of grade eleven students in the field of derivative in Bhutan - Kado Kado; Nedup Dorji; Nim Dem; Dorji Om (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
Given the increasing diversity of students academically and culturally, educators are being called upon to accommodate students' diverse learning requirements through differentiated instruction strategies. In Bhutan, the Ministry of Education recently mandated the implementation of a differentiated instruction strategy in the K-12 curriculum. From this perspective, this study attempted to ascertain the effect of differentiated strategies on grade eleven mathematics students within the framework of the pre_test and post_test quasi-experimental research method. 64 grade eleven students participated in this study. The concept of derivative was taught using a differentiated instruction strategy for the experimental group (N=32) while a conventional one-size fits-all strategy was used for teaching the control group (N=32). A Conceptual Understanding Test on the Derivative (CUTD) was administered as pretest and posttest groups to examine the differences in their learning achievements. A t-test analysis of the pretests indicated no significant differences, indicating that the experimental and control groups' learning abilities on the concept of the derivative were roughly comparable. However, a statistically significant difference in favour of the experimental group over the control group was discovered in the post test analysis. It was recommended that Mathematics teachers and educators should embrace the use of differentiated instruction while teaching and learning derivative.The researchers also recommended that differentiated education be used over a prolonged period of time and with a larger sample size.